The Image of the Tiger in Thomas Mann's Tod in Venedig - Ford P. Parkes (Studies in 20th & 21st Century Literature, 1978)
Mann integrates the image of the tiger (according to Nietzsche a concomitant of the Dionysian) that is associated with Aschenbach into Tod in Venedig, commencing with the poet's anticipatory vision. Throughout the course of the novella, the city becomes Aschenbach's envisioned jungle. Of particular significance is the triangular relationship between the viewer, the birds, and the tiger in the vision,which is found again at the end of the novella. Here, there are many repetitions of expressions suggestive of the triangular relationship found in Aschenbach's vision. The tiger in the vision, repeatedly mentioned or alluded to in Tod in Venedig, remains crouching and makes no move until the conclusion. Here, then, this «open» aspect is resolved: Aschenbach, whose latent Dionysian side is represented by the tiger on the mythical level, ultimately dies. Citing Euripides' Bacchae, which, as Manfred Dierks demonstrated, served as a «structural model» for Tod in Venedig, we can say that just as Pentheus dons the bacchante's dress offered by Dionysus, Aschenbach symbolically assumes the garb of the tiger. Pentheus adopts the disguise to observe secretly Dionysus' bacchantes. The way in which Aschenbach tracks Tadzio is evocative of the manner in which a tiger tracks its prey. By assuming the female disguise Pentheus guarantees his own death. Aschenbach acts in a like manner to Pentheus. Finally, both protagonists begin in their respective stories as hunters and both end as the hunted.
Keywords: Thomas Mann; Tod in Venedig; tiger; Dionysis